2006
DOI: 10.2298/mpns0608356l
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical training in patients after myocardial infarction

Abstract: Prolonged physical training is beneficial for patients after myocardial infarction, because it improves cardiovascular functions and physical work capacity, improves angina threshold and the patient's general health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Heart rate and systolic BP were numerically smaller in the EXP group, which in this case constitutes a better result. The results are in accordance with the results obtained by other researchers46, 47 ) .…”
Section: Discussionsupporting
confidence: 93%
“…Heart rate and systolic BP were numerically smaller in the EXP group, which in this case constitutes a better result. The results are in accordance with the results obtained by other researchers46, 47 ) .…”
Section: Discussionsupporting
confidence: 93%
“…12 It has been reported that, regular physical exercise increases serum HDL-C and decreases serum TC, LDL-C and TG level among postmenopausal women. 13,14 Again, HDL-C transport excess cholesterol from peripheral tissues to the liver for excretion, a process known as reverse cholesterol transport 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training could represent an useful tool, not only for prevention but also for therapy of aging related diseases. In fact, prolonged exercise training is a recognized tool for rehabilitation of cardiovascular patients, in particular after myocardial infarction, by improving cardiovascular functions and physical work capacity (132), in prevention and treatment of several conditions related to endothelial dysfunction, by decelerating the aging processes of the arterial wall and of the endothelial functions (133). In particular, the effectiveness of prolonged and moderate exercise training could be explained by hormesis, defined as the life supporting beneficial effects resulting from the cellular response to single or multiple rounds of mild stress (4,(134)(135)(136)(137).…”
Section: Discussionmentioning
confidence: 99%